2010
DOI: 10.3945/ajcn.2010.29274
|View full text |Cite
|
Sign up to set email alerts
|

Use of dietary supplements among active-duty US Army soldiers

Abstract: Soldiers, like civilians, use large amounts of DSs, often in combination. Soldiers use more DSs purported to enhance performance than civilians use when matched for key demographic factors. These differences may reflect the unique occupational demands and stressors of military service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
152
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(172 citation statements)
references
References 18 publications
17
152
2
1
Order By: Relevance
“…A standardized taxonomy used in national surveys, such as National Health and Nutrition and Examination Survey, was used to categorize DSs (Bailey et al 2011). Participants were also queried about the use of sports drinks, bars or gels, and meal replacement beverages based on previous reports indicating they are frequently used by military personnel (Lieberman et al 2010). These nutritional products were analyzed separately, and not reported here, as they are not classified as a DS by the Dietary Supplement Health and Education Act of 1994.…”
Section: Surveymentioning
confidence: 99%
See 3 more Smart Citations
“…A standardized taxonomy used in national surveys, such as National Health and Nutrition and Examination Survey, was used to categorize DSs (Bailey et al 2011). Participants were also queried about the use of sports drinks, bars or gels, and meal replacement beverages based on previous reports indicating they are frequently used by military personnel (Lieberman et al 2010). These nutritional products were analyzed separately, and not reported here, as they are not classified as a DS by the Dietary Supplement Health and Education Act of 1994.…”
Section: Surveymentioning
confidence: 99%
“…From 2006-2007and from 2010-2011, data were collected from 989 and 1207 active-duty soldiers, respectively, to ascertain prevalence and patterns of DS use using a standardized survey tool, the Dietary Supplement and Caffeine Intake Survey of U.S. Army Active Duty Personnel (Lieberman et al 2010). The data obtained for the 2006-2007 study were collected at 11 locations (9 United States installations and 2 overseas sites).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Gore and colleagues (2010) explained that the United States Air Force has worked to improve fatigue countermeasures, such as developing duty hour limitations, improving sleeping conditions to control sound and light, and offering hypnotics to induce sleep when time permits. Despite these formal efforts to reduce fatigue among military personnel, recent surveys have found that, in addition to using prescription alertness-enhancing medications such as modafinil, deployed military personnel are also using over-the-counter stimulants (Lieberman et al, 2010). This finding has raised concerns among the medical community over the safety and efficacy of combining prescribed and over-thecounter stimulants.…”
Section: Introductionmentioning
confidence: 90%